Psoas muscle depletion during preoperative chemotherapy for advanced gastric cancer has a negative impact on long‐term outcomes after gastrectomy. Issue 1 (28th February 2021) - Horii, Nobutoshi; Kosaka, Takashi; Fujiwara, Ryo; Sato, Sho; Akiyama, Hirotoshi; Kunisaki, Chikara; Endo, Itaru
Abstract: Aim: The significance of sarcopenia in cancers has been widely recognized. However, few studies have focused on chronological changes in sarcopenia in cancer patients. This study aimed to clarify the clinical significance of changes in the psoas muscle area before and after preoperative chemotherapy. Methods: This study included 39 patients who underwent gastrectomy followed by preoperative chemotherapy for advanced gastric cancer between January 2010 and December 2016 in our hospital. The psoas muscle area was measured at the umbilical level before and after chemotherapy, and the relationship between its chronological changes and the long‐term prognosis was examined. Results: Patients were classified into two groups according to changes in the psoas muscle area before and after preoperative chemotherapy: remarkable muscle depletion and normal groups. No significant differences were observed in clinicopathological factors. Notably, the remarkable muscle depletion group included significantly more male patients ( P = .018) and showed a high weight loss rate ( P < .001). Although no significant difference was observed in the recurrence‐free survival between the two groups ( P = .484), overall survival was significantly worse in the remarkable muscle depletion group ( P < .001). Multivariate analysis for prognosis revealed that pathological stage III or higher ( P = .022) and decreased psoas muscle area ( P = .038) were independent prognostic factors. Conclusions: The present findings suggest that psoas muscle depletion during preoperative chemotherapy is a prognostic factor for poor long‐term outcomes in patients who underwent gastrectomy followed by preoperative chemotherapy for advanced gastric cancer.